The Influences of Green Attributes of Electronic Sphygmomanometer on Consumer’s Purchase Behavior - Lai, Y.H. (Archives of Business Research, 2020)
Background: In recent years, high blood pressure has been one of the top ten causes of death in Taiwan. Operating the sphygmomanometer regularly to observe changes in blood pressure, and to track and observe one’s own basic health. This study focuses on the specification which electronic sphygmomanometer manufacturer can provide during the design for green attributes that meet customer’s preference. The subject of this study is to explore the preference of green electronic sphygmomanometer attributes Including power-saving, carbon footprint, recyclable, safety, streamline design and green accreditation from potential green computer buyers. Methods: The data was gathered through online survey over a month period from April, 2020 to May, 2020. Data is collected from convenience samples. 101 valid respondents were used for the conjoint analysis. Results: As the main purpose of this study is to find out the most importance attribute of green electronic sphygmomanometer what customer prefers, the result shows that carbon footprint turns out as the most influential attribute with the average importance of 18.63%, although it may not be considered as the majority factor in the decision-making process, it still stands out since there are six attributes in comparison. Green accreditation is the second important attribute with 17.31%, followed by recyclability and power-saving with at 16.83% and 16.15% respectively. The last two attributes, streamline design and safety, are relatively less important with 15.81% and 15.28% respectively. Conclusions: This study attempts to integrate the relevant green electronic sphygmomanometer attributes into a comprehensive research model. The conjoint analysis and the model of purchase intention for green electronic sphygmomanometer s creates an important alternative view of the antecedents.